Proteomic analysis of Alzheimer's disease cerebrospinal fluid from neuropathologically diagnosed subjects - Maarouf, Chera L. (2009)
A crucial need exists for reliable Alzheimer's disease (AD) diagnostic and prognostic tests. Given its intimate communication with the brain, the cerebrospinal fluid (CSF) has been surveyed intensively for reliable AD biomarkers. The heterogeneity of AD pathology and the unavoidable difficulties associated with the clinical diagnosis and differentiation of this dementia from other pathologies have confounded biomarker studies in antemortem CSF samples. Using postmortem ventricular CSF (V-CSF) pools, two-dimensional difference gel electrophoresis (2D DIGE) analyses revealed a set of proteins that showed significant differences between neuropathologically-diagnosed AD and elderly non-demented controls (NDC), as well as subjects with non-AD dementias. The 2D DIGE system identified a set of 21 different protein biomarkers. This panel of proteins probably reflects fundamental pathological changes that are divergent from both normal aging and non-AD dementias.